Efficient Solar‐Driven Water Harvesting from Arid Air with Metal–Organic Frameworks Modified by Hygroscopic Salt. Issue 13 (4th February 2020) - Xu, Jiaxing; Li, Tingxian; Chao, Jingwei; Wu, Si; Yan, Taisen; Li, Wenchen; Cao, Biye; Wang, Ruzhu
Abstract: Freshwater scarcity is a global challenge threatening human survival, especially for people living in arid regions. Sorption‐based atmospheric water harvesting (AWH) is an appealing way to solve this problem. However, the state‐of‐the‐art AWH technologies have poor water harvesting performance in arid climates owing to the low water sorption capacity of common sorbents under low humidity conditions. We report a high‐performance composite sorbent for efficient water harvesting from arid air by confining hygroscopic salt in a metal–organic framework matrix (LiCl@MIL‐101(Cr)). The composite sorbent shows 0.77 g g −1 water sorption capacity at 1.2 kPa vapor pressure (30 % relative humidity at 30 °C) by integrating the multi‐step sorption processes of salt chemisorption, deliquescence, and solution absorption. A highly efficient AWH prototype is demonstrated with LiCl@MIL‐101(Cr) that can enable the harvesting of 0.45–0.7 kg water per kilogram of material under laboratory and outdoor ambient conditions powered by natural sunlight without optical concentration and additional energy input. Abstract : A composite sorbent for efficient water harvesting from dry air is prepared by confining a hygroscopic salt in a metal–organic framework matrix (LiCl@MIL‐101(Cr)). This composite sorbent works efficiently under outdoor ambient conditions powered by natural sunlight without additional energy input.